2017
DOI: 10.1016/j.asjsur.2015.09.003
|View full text |Cite
|
Sign up to set email alerts
|

Internal hernia after laparoscopic gastrectomy with Roux-en-Y reconstruction for gastric cancer

Abstract: Retrocolic RY with appropriate closure of defects can reduce IH incidence at Petersen's defect and at jejunojejunostomy mesenteric defect. Although the IH incidence at the transverse mesocolic defect is not particularly high, the possibility of herniation through this defect should be kept in mind.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
17
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(19 citation statements)
references
References 28 publications
1
17
1
Order By: Relevance
“…Laparoscopic surgery has advantages such as a decrease in post-operative pain, decrease in adhesion rates, better cosmetic results, earlier recovery, and lesser duration of hospitalization (1,7). Many studies have demonstrated that the long-term results of laparoscopic surgery and open surgery in gastric cancers were similar (5,8).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Laparoscopic surgery has advantages such as a decrease in post-operative pain, decrease in adhesion rates, better cosmetic results, earlier recovery, and lesser duration of hospitalization (1,7). Many studies have demonstrated that the long-term results of laparoscopic surgery and open surgery in gastric cancers were similar (5,8).…”
Section: Discussionmentioning
confidence: 99%
“…The reasons for this situation include the decrease in mesenteric fat tissue because of postoperative weight loss, lesser amount of adhesions following laparoscopic surgery, leaving a longer Roux limb, and the . Internal herniation after laparoscopic gastric resection can be seen at any time after surgery, but the prevalence increases after the first year (1,4,5). In a study by Kelly et al (3), the authors stated that the rate of internal herniation following laparoscopic total gastrectomy was 22% at the end of an average of 22.4-month follow-up period.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, majority of patients that require bowel resection recover well according to various reports in the literature. Three cases of short gut syndrome and four cases of mortality have been reported 2 6 9. Depending of the location of internal hernia, a primary repair is usually performed for Petersen's defect, jejunojejunostomy mesenteric defect and transverse colon mesocolic defect with nonabsorbable sutures.…”
Section: Discussionmentioning
confidence: 99%